e-Government - Satyanarayana, J. (New Delhi, 2004)
This book is a masterly analysis of e-government and its benefits, role of people, process and technology in e-government, public-private partnership models, -government standards, and issues relating to security, digital divide, and cyber law.
Keywords: E-government-Benefits